The urban expansion of Chapecó – SC and the role of territorial social agents - Cancelier, Janete Webler; Chasqui, Jéssica Wendy Beltran; Zanon, João Silvano; Menezes, Leandro Jesus Maciel de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this study, we attempt to understand the processes that influence the dynamics of urban spatial growth of Chapecó - SC. The analysis was focused on urban space, covering the period relating to 2004/2014. The main objective was to analyze the trends of urban growth Chapecó and its conformity with the Master Plan of Chapecó. Specifically, it was found in the City Hall of Chapecó forecast locals for the current and future housing projects, after the implementation of the Master Plan, there was a trend of urban growth and the minimization of rural areas, we identified actions taken by the municipal government that will curb occupancy in areas not covered by the Master Plan for urban space, the role of territorial social agents, as well as the influence of corridors of centrality to the formation of new settlements in the urban space Chapecó. This article uses as a method of research a qualitative approach. The analyzes and discussions in this study demonstrate that territorial urban growth of Chapecó has occurred mainly in the suburbs, where infrastructure services are disabled.